A taxonomic revision of the genus Capparis (Capparaceae) in New Caledonia. Issue 4 (2nd October 2017) - Fici, S.
ABSTRACT: A revision of the genus Capparis has been carried out in New Caledonia, a global biodiversity hotspot with a high rate of endemism in its vascular flora. The taxonomic treatment of Capparis in this area required study because of some incompletely known taxa and deviating forms. Based on morphological and distributional investigations carried out on historical and recent herbarium collections, four species are recognised in New Caledonia: C. spinosa, belonging to sect. Capparis ; C. quiniflora, belonging to sect. Monostychocalix ; and C. parvifolia and C. artensis, both belonging to sect. Busbeckea . Capparis spinosa is represented by subsp. cordifolia, a taxon widespread in several Pacific islands, for which only scanty collections from the Loyalty Islands have been examined. Capparis quiniflora, widely distributed from the Malesian Region to Australia, is present along the coast and lowlands of New Caledonia on various substrata up to c. 250 m elevation. Capparis parvifolia is endemic to Mont Kaala, North Province of New Caledonia, where it is reported on ultramafic substrata from c. 100 to 800 m. Capparis artensis, known from New Caledonia and Vanuatu, is widespread prevalently on ultramafic substrata from sea level to c. 700 m. A nomenclatural novelty, C. artensis var. dielsiana comb. et stat. nov., is here proposed and seven lectotypes are designated. A key to species is provided, along with descriptions, distributions and autecological data. Capparis loranthifolia var. bancroftii, formerly recorded from a single mountain range of New Caledonia, is excluded from the flora of the island.